Kampo patterns and radiology in children receiving choreito for hemorrhagic cystitis after hematopoietic stem cell transplantation. Issue 2 (October 2016) - Kawashima, Nozomu; Sekiya, Yuko; Narita, Atsushi; Kamei, Michi; Muramatsu, Hideki; Nishio, Nobuhiro; Hama, Asahito; Ito, Yoshinori; Takahashi, Yoshiyuki; Kojima, Seiji
ABSTRACT: Aim: Choreito reduces the disease burden of hemorrhagic cystitis (HC) in children undergoing hematopoietic stem cell transplantation, but the underlying Kampo mechanism has not yet been clarified. To obtain pathophysiological insights, the present study evaluated changes in Kampo patterns and genitourinary imaging during choreito treatment. Methods: Ten consecutive children with late‐onset HC after stem cell transplantation were treated with choreito. Kampo patterns and computed tomography (CT) before and after choreito treatment were retrospectively analyzed. Results: Ten children with a median age of 9.7 years (range, 5.4–14 years) were diagnosed with late‐onset HC; 9 had BK virus and 1 had adenovirus. The median duration from the beginning of choreito intake to complete resolution was 12 days (range, 4–28 days). All 10 children fulfilled the Kampo pattern of Bladder damp–heat at diagnosis; all had heat and/or hardness in the lower abdomen, and 8 children had a slippery pulse. CT was obtained in 4 of the 10 children at the time of diagnosis, all of which showed bladder wall thickening and perivesical inflammation. After choreito treatment for a median of 26 days (range, 8–40 days), none of the children had any sign of damp–heat, which coincided with the disappearance of perivesical inflammation, as confirmed on CT. Conclusion: Lower abdominal heat/hardness with a slippery pulse may reflect damp–heat accumulation in the lower energizer, causing HC. Improvement in these examinations can be used as a surrogate response marker in choreito treatment for HC, which should be confirmed in future prospective studies.